TEKNIK AUDIT INVESTIGATIF, PENGALAMAN DAN PROFESIONALISME AUDITOR PADA PENGUNGKAPAN KECURANGAN : KECERDASAN SPIRITUAL SEBAGAI PEMODERASI - Dinda Larasati; Andreas Andreas; Rofika Rofika (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2020)
This study aims to determine the effect of investigative audit techniques, auditor experience and auditor professionalism on the disclosure of fraud with spiritual intelligence as a moderating variable. The data used in this study are primary data with a questionnaire as an instrument. The number of samples in this study were 60 respondents. Hypothesis testing in this study was carried out using the statistical test t. Data analysis techniques used in this study are multiple linear regression analysis and moderation regression analysis using the Statistical Product and Service Solution (SPSS) data processing software version 17.0 for windowS. The results of this study indicate that investigative audit techniques have a significant effect on disclosure of fraud. While the auditor's experience and auditor professionalism have no effect on disclosure of fraud. Moderate regression analysis shows that spiritual intelligence can moderate investigative audit techniques, auditor experience and auditor professionalism on disclosure of fraud